Analysis of the Justification for the Criminalization of Bestiality Based on Pancasila and the Morality of the Indonesian Nation - Isnawan, Fuadi (Jurnal Ius Constituendum, 2025)
This research explores the justification for criminalizing bestiality in Indonesia, emphasizing the moral and ethical values embedded in Pancasila. Triggered by the infamous case of an orangutan named Pony, subjected to sexual exploitation, the study highlights significant gaps in the Indonesian legal system. While Article 302 of the Criminal Code addresses physical abuse, it fails to explicitly criminalize bestiality, leaving such acts unregulated. Using a normative juridical method, the research integrates Pancasila’s principles of humanity, justice, and animal welfare as the moral foundation for legal reform. Pancasila promotes respect for all living beings, viewing bestiality as a violation of its core principles. The findings reveal significant enforcement challenges, including the private nature of the crime, the lack of witnesses, and the inability of animal victims to provide testimony. Forensic evidence, such as histopathology and DNA analysis, is critical but often hindered by limited training among law enforcement and veterinarians. Additionally, societal taboos and inadequate legal education exacerbate public unawareness of bestiality as a criminal offense. This study advocates for comprehensive public legal education, specialized training for law enforcement on forensic techniques and evidence management, and collaboration with veterinary experts to ensure effective enforcement. These measures aim to uphold animal welfare and align legal policies with Indonesian societal and ethical values